Masiahah Mursalah: Ruh Hukum Administrasi Negara dalam Perspektif Islam - Amir Muallim (Fakultas Hukum Universitas Islam Indonesia, 2003)
The spirit of State Administration is extremely identical to the concept of masiahah mursalah on the methodology of determining of Islamic Law it self. The crucial role taken part by theLaw of State Administration is also taken by masiahah mursalah.